A Comparison of Alexandre Popov and Michael Klim at 75 m of the 100 m Final at the 1998 Perth World Championships - Rushall, B. S.
Video pictures (18 frames) and the appropriate technical/ biomechanical explanations in a comparison of Alexandre Popov and Michael Klim at 75 m of the 100 m Final at the 1998 Perth World Championships. The underwater pulling actions, the recovery actions, and the timing of left-arm and right-arm phases are different between the swimmers. Alexandre Popov demonstrates a theoretically more desirable form of technique. It is testimony to the exceptional natural strength of Michael Klim that his performance levels can be so close to those of Alexandre Popov given the shortcomings in his technical skills. One is set to wondering to what would result if Michael Klim made the necessary adjustments to his technique.